Semi-Supervised HyperMatch-Driven Cross Temporal and Spatial Interaction Transformer for Hyperspectral Change Detection - Yixiang Huang; Lifu Zhang; Wenchao Qi; Ruoxi Song; Changping Huang; Yi Cen (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2024)
Hyperspectral images are valuable for precise land cover change detection in a consistent area over time. Nevertheless, supervised methods for hyperspectral change detection face limitations due to insufficient labeled samples. Additionally, current deep learning-based approaches often neglect critical feature interactions across temporal, spatial, and spectral domains. To address these challenges, we introduce a semisupervised model called the HyperMatch-based Cross Temporal and Spatial Interaction Transformer (CTSIT) for hyperspectral change detection. The key contributions of this study are as follows: Introduction of the HyperMatch training schedule, which relies on weak-to-strong consistency, to enhance feature extraction using both labeled and unlabeled data. Then, the contribution of the Cross Temporal Bidirectional Attention module to emphasize bidirectional temporal interactions and resemblances. Finally, Introduction of the Spatial and Spectral Attention module, which includes the Dense Cross Spatial Attention and Spectral Attention modules, to capture long-range densely spatial interactions and internal spectral similarities. Extensive comparative experiments conducted on three mainstream hyperspectral change detection datasets confirm the effectiveness and superiority of the proposed HyperMatch-based CTSIT in utilizing both labeled and unlabeled samples. For instance, the training ablation demonstrates that this method significantly outperforms most existing state-of-the-art hyperspectral change detection methods, even with a significantly smaller number of samples.